5G beamforming techniques for the coverage of intended directions in modern wireless communication: in-depth review - Rao, Leevanshi; Pant, Mohit; Malviya, Leeladhar; Parmar, Ajay; Charhate, Sandhya Vijay (International journal of microwave and wireless technologies, 2021)
The growing need of the compact and portable antennas with high speed and low latency wireless communication is the present and future demand of the voice over Internet protocol, on-demand bandwidth, and multimedia applications. Fifth-generation (5G) covers certain low-frequency bands under 6 GHz spectrum, and most of the high-frequency bands under 60 GHz. 5G is the part of the millimeter wave spectrum (30–300 GHz) and is introduced to overcome the problem of spectrum shortage due to exponential enhancement of wireless applications in industry, medical, airborne, radar, satellite, and research fields. The International Telecommunication Union's objective of wireless communications promises to provide higher data rates up to 10 Gbps for 5G mobile users and connectivity to the artificial intelligence devices, along with high spectral efficiencies and enhanced coverage. The users for the 5G require around 5 and 50 Gbps of data rates for low and high mobility, respectively. Beamforming in 5G is the modern powerful technique for the coverage of the intended user/direction using the narrow beam width radiation patterns. A brief survey on 5G beamforming techniques, i.e. analog, digital, hybrid, switched, and adaptive etc. and its types, working algorithms, design of compact antennas, gain, and size/type of the substrates is carried out in this paper. The study of the hybrid coupler, branchline coupler, Wilkinson power divider, and Butler matrix in beamforming is required for 5G smart antennas. Different beam widths like ±15, ±35, ±45, and ±55° etc. are produced for the intended directions using a variety of beamforming techniques. From lower to higher frequency band beamforming applications with Roger's Duroid 4003/4350/5880, tectonic, and aluminum oxide dielectric substrates are discussed here. Various beamforming techniques with their merits, demerits, and applications are included in the paper for the knowledge extension of the beamforming antenna designers and research community.